Prevalência do vírus JC e correlação com manifestações neurológicas em pacientes portadores do HIV-1 ou com AIDS internados no Hospital Universitário João de Barros Barreto, Belém, Pará - LOPES, João da Cunha (2023)
In the Acquired Immunodeficiency Sindrome (AIDS) occur neurological symptoms due to the infectious process by the Human Imunodeficiency virus (HIV) and caused by co-infection for other agents as well. Among these agents is JC virus (JCV), which is related to the presence of specific neurological signals and symptoms across a spectrum of neurologic states called Progressive Multifocal Leukoencephalopathy (LMP), serious, fatal demyelinating disease of the central nervous system, that usually appear immunocompromised specially in the setting of AIDS. Currently, with the use of Higly active antiretroviral therapy (HAART) the classical LMP became less comom giving place to weak and moderate symptoms of the presence of JCV x HIV co-infection. This way the JCV co-infection early diagnosys is important and can be in a very easy way with the urine examination of these patients featuring the polimerase chain reaction (PCR) to detect the viral genome presence. The present work analyse urine samples in patients with AIDS to JCV detection and then try to associate the JCV presence with the neurologic manifestations on these patients. This way it was collected urine samples from 50 HIV infected patients and analysed about the presence of JCV genome by PCR technique that have shown 20 of them (40%) coinfected by JCV. Then, all of them from the two groups, monoinfected (only HIV infection) and double infected (HIV x JCV infection) have their hospital register analysed about the prevalence of the following neurological signals and symptoms: headache, walk disability, motor discordination, balance disability, convulsion, language disability, demency, hemiplegy or hemiparesy and paresthesy. As result it was observed that the monoinfected group (only by HIV), 17 56,65%) presented some of the avaluated neurological symptoms once 13(43,35%) kept without any of it. On the other hand, in the double infected group it was observed that 13(65%) presented it, once 7(35%) kept without any neurological symptoms. That was also observed that the most frequent of these symptoms were: headache 20(40%), paresthesias 7(14%) and hemiparesia 9(18%). These results demonstrate that the development of neurological symptoms were not significantly influenced by the presence of co-infection HIV x JCV.